Pharmacokinetic drug interactions and adverse consequences between psychotropic medications and pharmacotherapy for the treatment of opioid dependence. - Saber-Tehrani, Ali S; Bruce, Robert Douglas; Altice, Frederick L (The American journal of drug and alcohol abuse, 2011)
Psychiatric comorbidities among opioid-dependent patients are common. Many medications used to treat both conditions are metabolized through complimentary cytochrome P450 isoenzymes. When medication-assisted treatment for opioid dependence is concurrently used with psychotropic medications, problematic pharmacokinetic drug interactions may occur.
Keywords: Drug Interactions; Humans; Narcotic Antagonists; Opioid-Related Disorders; Psychotropic Drugs